Analisis Potensi Kadar Kalium dan C-Organik dari Kompos Organik Berbahan Dasar Eceng Gondok, Batang Pisang Dan Kotoran Kambing - Handoyo, Rivaldo; Mualim, Mualim (Poltekkes Kemenkes Bengkulu, 2025)
This study aims to analyze the potential levels of Potassium (K) and Organic Carbon (C-organic) in organic compost made from water hyacinth (Eichhornia crassipes), banana stem (Musa paradisiaca), and goat manure, with EM4 as an activator Method : A quasi-experimental design was applied using four treatments: X0 (control), X1 (3 kg water hyacinth, 1 kg banana stem, 1 kg goat manure), X2 (2 kg water hyacinth, 2 kg banana stem, 1 kg goat manure), and X3 (1 kg water hyacinth, 3 kg banana stem, 1 kg goat manure). The fermentation process lasted 30 days, with routine monitoring of temperature, pH, and moisture Results : Laboratory analysis confirmed that all treatments met the Indonesian National Standard SNI 19-7030-2004 (Potassium ≥ 0.20% and Organic Carbon ≥ 9.80%). Treatment X1 showed the highest Potassium content (0.79%), while X3 showed the highest Organic Carbon content (23.12%) Suggestion : This research can be used as a combination of local materials that can produce high quality, environmentally friendly compost and contribute to the sustainable use of organic waste.